AN ANALYSIS OF FACTORS AFFECTING THE HIGH RADON CONCENTRATION IN DIFFERENT TYPES OF HOUSES - Gulan, Ljiljana (Bulletin of Natural Sciences Research, 2017)
This paper presents an analysis of indoor radon measurements carried out in municipality of Zubin Potok, northwestern part of Kosovo and Metohija. Annual measurements in two rooms of each house were performed by solid state nuclear track detectors commercially known as Gammadata. Average indoor radon concentration in different type of houses varied from 29-326 Bq/m3. A different year of house’s construction including various types of building materials were selected for survey. A detail analysis showed that the differences in radon concentration occur between various building materials used for construction, flooring level, type of room and behavior of inhabitants. It was found that building materials in some houses contribute additionally to indoor radon.
Keywords: building materials; house; Indoor radon concentration